Update on penile sparing surgery for penile cancer. Issue 1 (January 2022) - Anastasiadis, Eleni; Ayres, Benjamin; Watkin, Nick
Abstract : Purpose of review: Penile sparing surgery (PSS) is considered the standard of care in penile cancer where appropriate, as preservation of the penis may enable the patient to maintain urinary and sexual function. This review will focus on the latest developments over the past two years. Recent findings: In this review, we discuss the latest findings in oncological outcomes in PSS, specifically glansectomy. We also introduce technology that may be useful in improving the precision of surgical resection margins in PSS. Finally, we consider the value of patient-reported outcome measures (PROMs) and consider how research in this area can be improved. Summary: A recent study has found a correlation between local recurrences (LR) and worse overall and cancer-specific survival in glansectomy, which challenges the belief that LR do not confer worse oncological outcomes. Despite numerous studies evaluating PROMs in penile cancer/PSS, few of these studies provide quality evidence of the 'supportive care needs'. A shift in research is required to identify those men at most risk of distress and to identify ways to support men diagnosed with penile cancer.